2017
DOI: 10.1016/j.eurpsy.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of motivational impairment: 12-month follow-up of the randomized-controlled trial on extended early intervention for first-episode psychosis

Abstract: BackgroundAmotivation is prevalent in first-episode psychosis (FEP) patients and is a major determinant of functional outcome. Prediction of amotivation in the early stage of psychosis, however, is under-studied. We aimed to prospectively examine predictors of amotivation in FEP patients in a randomized-controlled trial comparing a 1-year extension of early intervention (Extended EI, 3-year EI) with step-down psychiatric care (SC, 2-year EI).MethodsOne hundred sixty Chinese patents were recruited from a specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
3
3
0
Order By: Relevance
“…In addition, we observed differential patterns of connections of amotivation and DE with other variables, lending support to the validity of the two-factor structure of negative symptoms (Messinger et al, 2011;Liemburg et al, 2013). For instance, in line with the literature (Strauss et al, 2013;Chang et al, 2017), our results showed that premorbid adjustment was linked to amotivation but not DE. Critically, we found that psychosocial functioning was most strongly connected to amotivation in the network, and was only weakly related to DE.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we observed differential patterns of connections of amotivation and DE with other variables, lending support to the validity of the two-factor structure of negative symptoms (Messinger et al, 2011;Liemburg et al, 2013). For instance, in line with the literature (Strauss et al, 2013;Chang et al, 2017), our results showed that premorbid adjustment was linked to amotivation but not DE. Critically, we found that psychosocial functioning was most strongly connected to amotivation in the network, and was only weakly related to DE.…”
Section: Discussionsupporting
confidence: 92%
“…Third, even though standard treatment and intervention treatment were ensured by different specialists, the evaluation was conducted by the same assessors, which may cause performance bias. In contrast, the effectiveness of the intervention could be biased by the short duration of the intervention treatment in this study; other studies have demonstrated the importance of extended interventions, confirming better effectiveness with prolonged early intervention in psychosis (67). Lastly, in this study, we did not include any cognitive testing which could affect clinical and functional outcomes.…”
Section: Limitations and Strengthssupporting
confidence: 39%
“…Thirty-five studies comprising 3180 participants examined the severity of depressive symptoms (Binder et al ., 1998; Zalsman et al ., 2003; Kampman et al ., 2004; Bendall et al ., 2008; Arranz et al ., 2009; Chen et al ., 2009; Strous et al , 2006; Strous et al ., 2009; Barrett et al ., 2010; Cotton et al ., 2010; Roche et al ., 2010; Upthegrove et al ., 2010; Chang et al ., 2011; Pena et al ., 2011; Shoval et al ., 2011; Riedel et al ., 2012; Stowkowy et al ., 2012; Zhao et al ., 2012; Allott et al ., 2013; Tosato et al ., 2013; Arrasate et al ., 2014; Chang et al ., 2014; Stouten et al ., 2014; Chang et al ., 2015; Emsley et al ., 2015; Noto et al ., 2015; Ruggeri et al ., 2015; Sanchez-Gistau et al ., 2015; Ebdrup et al ., 2016; Garcia et al ., 2016; Pawelczyk et al ., 2016; Chang et al ., 2017; Herniman et al ., 2017; Lee et al ., 2017; Zabala et al ., 2017). Three studies reported statistics by sub-group (Binder et al ., 1998; Tosato et al ., 2013; Pawelczyk et al ., 2016), totalling 38 samples.…”
Section: Resultsmentioning
confidence: 99%